Feasibility, acceptability, and fidelity evaluation of a contextualised physical activity and diet intervention for hypertension control in rural South African adults - Kganetso Sekome; Francesc Xavier Gómez-Olivé; Hellen Myezwa; Dale W. Esliger; Lauren B. Sherar (PLoS ONE, 2026)
Despite the known benefits of physical activity and diet modifications for hypertension control, adults in rural South African settings still have high levels of uncontrolled hypertension. This paper outlines an intervention that targets adjusting routine physical activity and diet practices for hypertension control in adults from rural South Africa (HYPHEN). The intervention involved a structured group education, individualised physical activity education, and individualised dietary education. We aimed to evaluate the feasibility, acceptability, and fidelity of HYPHEN for adults aged 40 years and older living with hypertension in rural South Africa. Feasibility was measured by assessing recruitment and retention rates. Acceptability was assessed through interviews after the intervention using pre-determined themes of perceived expectations, benefits, motivation, and barriers concerning the intervention. Fidelity was evaluated by intervention adherence, dosage, quality, and participant responsiveness. Participants were also asked to rate their overall satisfaction on a Likert scale out of 10. Our study demonstrated high level of feasibility, acceptability, and fidelity. Thirty participants were successfully recruited (100% of target), 28 (93%) participants were retained, and 28 (93%) provided complete data. Qualitative data demonstrated high acceptability, with participants reporting that the intervention met expectations, provided benefits, motivated continued engagement, and involved few barriers. Intervention fidelity was high with all three components carried out as planned, minor dosage adjustment, high delivery quality, and 100% participant engagement. The average rating on the Likert scale was 8.6/10 (SD = 2.55). HYPHEN is a feasible and acceptable intervention for hypertension control. Trial registration: Pan African Clinical Trial Registry (pactr.samrc.ac.za) PACTR202306662753321. Retrospectively registered on 29 June 2023.